Examining the Relationship between Self-Reflection and Academic Achievement in Problem-Based Learning - Sahasrabudhe, Chetan (Journal of Engineering Education Transformations, 2022)
Problem-based learning (PBL) has been an essential pedagogical strategy in teaching and learning Architectural Design since the early days of the discipline. As with any pedagogical strategy, multiple factors impact the learning outcomes in a PBL-based classroom. Among them, ‘reflection’ features frequently in the literature. This essay examines the relationship between reflection or more specifically, self-reflection and academic achievement in PBL. The examination is based on Reflective essays written by the students at the end of the semester. Reflective Essays are correlated with academic achievement in the subject of architectural design. The essay concludes that there is a strong correlation between self-reflection and academic achievement.